2015
DOI: 10.1016/j.tetasy.2015.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Chiral primary amino alcohol organobase catalysts for the asymmetric Diels–Alder reactions of anthrones with maleimides

Abstract: Simple chiral TES-amino alcohol organocatalysts containing a bulky silyl [triethylsilyl: TES] group on oxygen atom at γ-position were designed and synthesized as new organocatalysts for the enantioselective Diels-Alder (DA) reaction of anthrones with maleimides to produce chiral hydroanthracene DA adducts (up to 99% yield with up to 94% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Excellent covalent and non‐covalent organocatalysts have been developed for use in a wide range of reactions . Most recently, we reported that a primary β‐amino alcohol acts as an efficient organocatalyst in some reactions . The enantioselective aldol reaction using organocatalysts is recognized as one of the most powerful carbon–carbon bond‐forming reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Excellent covalent and non‐covalent organocatalysts have been developed for use in a wide range of reactions . Most recently, we reported that a primary β‐amino alcohol acts as an efficient organocatalyst in some reactions . The enantioselective aldol reaction using organocatalysts is recognized as one of the most powerful carbon–carbon bond‐forming reactions .…”
Section: Introductionmentioning
confidence: 99%
“…First, squaramides 8–15 were synthesized according to the literature 44–58 . Squaramide ligands 8 – 15 was easily synthesized from the reaction of chiral amine or amino alcohols and diethyl squarate (Figure 1, Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…The squaramide organocatalysts 8-15 were synthesized according to literature procedures. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Unsymmetrical squaramide organocatalysts 8-13 were synthesized from squarate monoamide ester 7 via a multistep procedure. In the first step, the squaric ester 5 reacted with an equimolar amount of 6 in ethanol to the squarate monoamide ester 7.…”
Section: General Procedures For the Synthesis Of Catalysts 8-15mentioning
confidence: 99%
“…Diels–Alder cycloaddition between anthrone and N ‐substituted maleimides to construct cage anthrone derivatives is one of the important reactions, because the resulting products could be utilized as synthetic intermediates for the preparation of some unsaturated lactams with antipsoriatic and antiproliferative biological activities . To examine this cycloaddition we designed and synthesized simple chiral trialkylsilyl amino alcohol organocatalysts, each containing a bulky trialkylsilyl group on the oxygen atom at the α‐position (Scheme ) . Diels–Alder cycloaddition between anthrone ( 22 ) and N ‐substituted maleimides 23 in the presence of our synthesized simple β‐amino alcohols 15 and 17 and our trialkylsilyl amino alcohol catalysts 18 – 21 was examined (Scheme ).…”
Section: Diels–alder Cycloadditionmentioning
confidence: 99%
“…Diels–Alder cycloaddition between anthrone ( 22 ) and N ‐substituted maleimides 23 in the presence of our synthesized simple β‐amino alcohols 15 and 17 and our trialkylsilyl amino alcohol catalysts 18 – 21 was examined (Scheme ). Out of all these catalysts, triethylsilyl amino alcohol 18e was found to be the best, affording the Diels–Alder adducts with excellent chemical yields (99 %) and good enantioselectivities (up to 94 % ee ) . Taking advantage of organobase‐type catalysts, we also used several other organobase catalysts to promote this reaction …”
Section: Diels–alder Cycloadditionmentioning
confidence: 99%